Perception of Quality Attributes in Short Agri-food Chains - Scalco, Andréa [UNESP]; Ganga, Gilberto; Oliveira, Sandra [UNESP]; Piao, Roberta; Pigatto, Gessuir [UNESP]; Machado, João Guilherme [UNESP] (De Gruyter, 2021)
This paper aims to identify quality attributes in products from short agri-food chains, highlighting the perception of these attributes in three types of short chains (face-to-face, spatial proximity, and spatially extended). We conducted a survey with 904 consumers in six distribution channels. The results indicate that the perception of quality attributes for consumers in short agri-food chains is not homogeneous. The results also shed light on the mechanisms adopted for transmitting information from producer to consumer in spatially extended short chains, restricted to the use of seals or brands.
Keywords: Agri-food chains; Product quality; Quality turn